Weed Control in Strawberry - William M. Stall (EDIS)
Revised! HS-196, a 3-page fact sheet by William M. Stall, provides pesticide recommendations for strawberry production. Includes a table listing chemical weed controls for strawberry in Florida. Published by the UF Department of Horticultural Sciences, November 2007.